EVEKTIVITAS PENGGUNAAN TIRFOR DAN KATROL TUAS PADA PENEBANGAN JATI DI JAWA TENGAH - Maman Mansyur Idris; Zakaria Basari; Soenarno Soenarno (Jurnal Penelitian Hasil Hutan, 1985)
The study  of  tirfor  and lever block  effectiveness in teak felling was conducted at the Perum Perhutani  (The Forest State  Corporation) Unit I Central Java on June 1982 and July  1983. Both felling equipments were used cut the press down  to the desired directions.The purpose  of  the  study  is to find  out  the effects  of tirfor and lever block  on log damager in felling actives.  The study  was carried out  in a three  locations  with  different slopes  i.e. 0 -10% and 11 – 30%.The result  indicates  that on  the  11 - 30% slope,  the  tirfor  reduces 5.25%  log damages compared  with  that of the lever block.  It is concluded that in sloped areas tirfor is more efective  then lever block.